The Graduate Experience: Living and Studying Abroad (A Case Study) - Rosario Hernández Castañeda (Universidad Autónoma de Baja California, 2008)
This article is a qualitative case study describing the experience of Angélica an international graduate student from Latin America, who received her doctorate at the University of New Mexico in the United States. Her case demonstrated how administrators and faculty learn about the experience and struggles endured by international students, especially those who learned English a short time before admission to graduate studies. While a single case is understandably idiographic in nature and inevitably requires a larger sample, from the analysis of Angélica's case and the analysis of the relevant literature common topics emerged persuading me to conclude that the issues that commonly impact the life of international students have to do with: 1) second language problems; 2) the quality of academic advisement received; 3) the availability of financial support; 4) the level of integration into their academic program; and 5) the level of cultural adjustment in their host country.